Legal guarantees for litigants before the military judiciary in Iraq (a comparative analytical study) - Suzan Othman Kader; Ali, Bilal Abdul-Jabbar Syed (Journal of Legal and Political Studies, 2021)
The military judiciary is the judicial body that considers a set of disputes between the military administration and one of the persons subject to the jurisdiction of this judiciary, due to the violation of any military text attributed to this person. In view of the organizational characteristics of military laws for relationships that differ in their nature from other ties regulated by law in civilian life, because military life needs to be controlled and linked, the nature of military justice has privacy as well, as it cannot be described as a purely criminal justice, nor It is purely disciplinary. Also, granting litigants before its courts a set of guarantees that are among the rights inherent and inherent to the human person, even if he is accused of a crime or a harmful act, because the rule stipulates that “the accused is innocent until proven guilty in a fair legal trial”, with what this rule requires. By providing a set of constitutional and legal guarantees that surround the idea of fair legal trials. Therefore, the research shed light on all of the foregoing and the researchers put the proposals at the end of it, the most important of which as we suggest to the Iraqi legislator the text in the Iraqi Military Criminal Procedure Code No. (22) of 2016 on the right of the accused to remain silent and we suggest that the text should be as follows (It is not permissible to force The accused before the military courts to speak or defend himself, and this is not considered a presumption against him). Also, amending the text of Article (43/First) of the Iraqi Military Criminal Procedure Code No. (22) of 2016 stating the reasons and cases of the secret military trial, as the Egyptian legislator did without being satisfied with the general texts.
Keywords: military judiciary military; administration; military justice; Military Criminal Procedure Code No 22 of 2011; Egyptian legislator